'Europe of the regions' an attempt to overcome antinomy of freedom and order: A reality or utopia - Kovačević Bojan (Međunarodni Problemi)
Since the beginning of the European integration process until the present day the states have given up some significant elements of their sovereignty transferring an increasing number of authorities to the European institutions. The extended framework within which the rules of the European game are determined also exerts a considerable impact on the regions as integral units of the present-day complex states. Politically and economically powerful regions are more and more independent in the contemporary European political and economic space. This has created a distorted picture of 'Europe of the regions' where the regions and European institutions will establish direct contacts, making the role of states superfluous. In this paper, the author endeavors to offer a theoretical historical and philosophic frame for consideration of the attempts to overcome the antinomy of freedom and order both in the past and in the present, particularly analyzing the position and role of the regions in the European Union political and economic system.